Harder Site : A Middle Period Bison Hunters' Campsite in the Northern Great Plains - Dyck, Ian G. (Book collections on Project MUSE., 1977)
Doctoral thesis, University of Alberta, 1976. An analysis and functional interpretation of the tools and debris found in a Middle Period bison hunters' campsite in the parklands of central Saskatchewan.